Electrospun SiO2/WO3/NiWO4 decorated carbon nanofibers for an efficient electrocatalytic hydrogen evolution. Issue 6 (3rd June 2019) - Zhu, Mengxuan; Sun, Jianhang; Li, Chuang; Han, Ce; Shan, Yuping; He, Jin; Jia, Jianbo; Wu, Wanmin; Yang, Guocheng
Abstract: The SiO2 /WO3 /NiWO4 composites modified carbon nanofibers (SiWNi-CNFs) were prepared by a facile electrospinning method with following carbonization process under nitrogen atmosphere. The as-obtained SiWNi-CNFs were characterized by transmission electron microscope (TEM), scanning electron microscope (SEM), X-ray photoelectron spectra (XPS), X-ray powder diffraction (XRD), FT-IR spectroscopy and Raman spectroscopy. As revealed by the electrochemical measurement, the SiWNi-CNFs prepared with SiW12 /NiAc2 molar ratio of 1:1 presented best hydrogen evolution activity with a small Tafel slope (48 mV dec −1 ) among all the as-prepared samples. Notably, the as-prepared catalysts exhibit a small onset potential (0.29 V vs. reversible hydrogen electrode), high current density and excellent stability. The experimental results pointed that the SiWNi-CNFs processes more efficient hydrogen evolution properties than that other contrast samples. This is due to the SiO2 /WO3 /NiWO4 composite modified on the surface of carbon nanofibers can generate numerous active sites from the synergistic effect of each component. At the same time, the intimate combination of ternary oxide and carbon nanofibers can accelerate the electron transfer, enhance the stability and hinder the aggregation of active components during the carbonization. Moreover, the net-like structure stacked by carbon nanofibers should render the exposure of active sites and facilitate the mass transport for the HER process.